Pengaruh Supply Chain Management terhadap Kualitas Produk (Makanan) dan Dampaknya pada Kinerja Bisnis di Rumah Makan Nur - Amelia, Maya; Sari, Preti Intan; Aisyah, Siti (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
The purpose of this study was to determine and analyze the effect of supply chain management (SCM) on product quality and its impact on business performance at Rumah Makan Nur. The approach used in this research is a quantitative and associative approach. The data analysis technique in this study used Multiple Linear Regression analysis techniques with a population of all consumer visitors and employees at Nur Restaurant and the sample of this study was 100 respondents. The data collection technique in this study used a questionnaire (questionnaire). Data processing in this study used the IBM SPSS Statistics 23 software program.The results of this study indicate that SCM Quality and Product Quality have a significant effect on Business Performance at Nur Restaurant. These results can be concluded that the better SCM will improve business performance through product quality at Nur restaurannt.